Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
Step-by-step explanation:
LHS = (sec x - tan x)(Sec x - tan x)
= sec² x - tan²x {(a +b)(a-b) = a² - b²}
[tex]= \dfrac{1}{Cos^{2} \ x}-\dfrac{Sin^{2} \ x}{Cos^{2} \ x}\\\\\\= \dfrac{1-Sin^{2} \ x}{Cos^{2} \ x}\\\\= \dfrac{Cos^{2} \ x}{Cos^{2} \x}\\\\= 1[/tex]
Hence proved.
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.